The large GTPase AtGBPL3 links nuclear envelope formation and morphogenesis to transcriptional repression - Reimann, Theresa; Müdsam, Christina; Schachtler, Christina; Ince, Semra; Sticht, Heinrich; Herrmann, Christian; Stürzl, Michael; Kost, Benedikt (Nature Plants, 2023)
Guanylate binding proteins (GBPs) are prominent regulators of immunity not known to be required for nuclear envelope formation and morphogenesis. Here we identify the Arabidopsis GBP orthologue AtGBPL3 as a lamina component with essential functions in mitotic nuclear envelope reformation, nuclear morphogenesis and transcriptional repression during interphase. AtGBPL3 is preferentially expressed in mitotically active root tips, accumulates at the nuclear envelope and interacts with centromeric chromatin as well as with lamina components transcriptionally repressing pericentromeric chromatin. Reduced expression of AtGBPL3 or associated lamina components similarly altered nuclear morphology and caused overlapping transcriptional deregulation. Investigating the dynamics of AtGBPL3-GFP and other nuclear markers during mitosis (1) revealed that AtGBPL3 accumulation on the surface of daughter nuclei precedes nuclear envelope reformation and (2) uncovered defects in this process in roots of AtGBPL3 mutants, which cause programmed cell death and impair growth. AtGBPL3 functions established by these observations are unique among dynamin-family large GTPases.
CRIS-Team WoS Importer:2023-05-26